Evaluation of the 90-Day Administration of Cyperus rotundus Tubers on Nrf2, SOD, and MDA Profiles by Flow Cytometry - Setiawan, Meddy; Lestari, Noviana Dwi; Agustini, Sulistyo Mulyo (Bogor Agricultural University, Indonesia, 2025)
Nuclear factor erythroid 2-related factor 2 (Nrf2), superoxide dismutase (SOD), and malondialdehyde (MDA) are components involved in the antioxidant system and the body's response to oxidative stress. The bioactive compounds of Cyperus rotundus tuber (CRT) have pharmacological effects as antioxidants and anti-inflammatory. This study aimed to evaluate the impact of CRT administration for 90 days on the profiles of Nrf2, SOD, and MDA. 24 male Wistar rats were used in this study and divided into 4 treatment groups: Control, dose 1 (300 mg/kg BW), dose 2 (600 mg/kg BW), and dose 3 (900 mg/kg BW). Oral administration of CRT was carried out for 90 days. On day 91, liver isolation was performed to determine the profiles of Nrf2, SOD, and MDA using Flow Cytometry. Statistical analysis using One-Way ANOVA with P<0.05 was conducted using SPSS. The administration of CRT to Wistar rats for 90 days did not induce toxic or harmful effects. The Nrf2 and MDA profiles did not show excessive activation with CRT administration. The SOD profile increased with D1 administration compared to the control and other doses. The administration of CRT for 90 days has the potential to be used as a natural alternative to address diseases related to oxidative stress.